Protecting AODV from Wormhole Attack in WSN (International Journal of Engineering and Computer Science, 2014)
Wormhole attack is a severe threat against ubiquitous sensor networks. Due to variety of proactive protocols used in the network DSDV does not exploit the large network. AODV is an effective routing protocol for networks that doesn’t maintain any routing tables at nodes which results in less overhead and more bandwidth. The connection setup delay is lower. MRT will work efficiently only when wormhole node will come in the path from source to destination. In this paper detection and isolation of the wormhole has been proposed. This approach is implemented using NS-2. The results and conclusions are shown in the paper.